2010
DOI: 10.1074/jbc.m110.172098
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Reduced Glucosylceramidase Activity in the Most Common Gaucher Disease Mutant, N370S

Abstract: Gaucher disease is caused by the defective activity of the lysosomal hydrolase, glucosylceramidase. Although the x-ray structure of wild type glucosylceramidase has been resolved, little is known about the structural features of any of the >200 mutations. Various treatments for Gaucher disease are available, including enzyme replacement and chaperone therapies. The latter involves binding of competitive inhibitors at the active site to enable correct folding and transport of the mutant enzyme to the lysosome. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…MD simulations can help us understand the effects of mutation on protein structure, which allow exploring how one amino acid substitution can create a ripple effect throughout the protein structure. Offman et al found a strong correlation between MD analysis and the experimental work on the molecular basis of the most common protein upon N370S mutation in causing Gaucher's disease [26,27]. Thus, we assume that MD simulation analysis might provide more reliable structural information upon CDK7 mutations.…”
Section: Introductionmentioning
confidence: 86%
“…MD simulations can help us understand the effects of mutation on protein structure, which allow exploring how one amino acid substitution can create a ripple effect throughout the protein structure. Offman et al found a strong correlation between MD analysis and the experimental work on the molecular basis of the most common protein upon N370S mutation in causing Gaucher's disease [26,27]. Thus, we assume that MD simulation analysis might provide more reliable structural information upon CDK7 mutations.…”
Section: Introductionmentioning
confidence: 86%
“…Generally, proteins that are unable to fold properly are identified by ER chaperones and returned to the cytosol for ubiquitin-dependent proteasomal degradation. Although several mutations produce the various phenotypes of GD, improper folding and subsequent degradation of mutant GCase by the ubiquitin-proteasome pathway seems to be a common mechanism that ultimately leads to cellular accumulation of glucocerebroside in many of these mutations (22). Previously, we found that the catalytic activity of GCase was not impaired by common mutations found in GD types I, II, and III, but that enzymatic activity was correlated with the concentration of the protein in the cell (6).…”
Section: Discussionmentioning
confidence: 99%
“…In 2003, the first crystal structure of GCase was solved; since then, additional crystal structures have been obtained for both the apoenzyme [1][2][3][4][5][6][7] and for complexes of the enzyme with a number of ligands [3,5,[8][9][10][11][12] under various experimental conditions (Table 8.1). Furthermore, the first crystal structure of the most common Gaucher disease mutation, N370S, was recently obtained, which, together with molecular dynamics studies, enhanced our understanding of the underlying molecular mechanisms that result in decreased enzymatic activity [7,13,14]. In this chapter, we give a general overview of the GCase crystal structures and summarize recent findings.…”
Section: Marc N Offman Israel Silman Joel L Sussman and Anthony H Futmentioning
confidence: 96%
“…In the molecular dynamics study, it was also predicted that NB-DNJ is able to stabilize a GCase-saposin C complex, which is a requirement for formation of a substrate-enzyme complex. A more thorough analysis of the predicted and experimental results was presented [14], which showed the potential of molecular dynamics simulations of GCase mutants to provide valuable information in the context of mutation-specific drug design [7,13,14]. Generally, two effects are thought to cause diminished activity: reduced catalytic activity and reduced lysosomal concentration.…”
Section: Wkl (2010): Structure Of Velaglucerase Alfamentioning
confidence: 98%